Characterization and cytotoxicity of clausenidin from Clausena excavata Burm f. and its effects on cell cycle regulation and apoptosis of liver (hepg2) and colon (ht29) cancer cell lines - Waziri, Peter Maitalata (2017)
Clausena excavata Burm. f. is a wild shrub from the Rutaceae family predominantly found in tropical Asia. The plant is traditionally used in the treatment of cancers; however, its mechanism of anticancer action is still unknown. Among phytochemicals present in C. excavata are alkaloids, coumarins and limonoid. Clausenidin, a pyranocoumarin isolated from C. excavata is postulated to have anticancer effects. Thus, the objective of this study is to determine the in vitro anticancer effect of clausenidin on the liver (HepG2) and colon (HT-29) cancer cell lines. The cytotoxicity and effect of clausenidin on the HepG2 and HT-29 cell cycles were determined via acridine orange/propidium iodide, reactive oxygen species (ROS), annexin V and cell cycle assays. DNA fragmentation and ultrastructural analyses, caspase-3 and -9 as well as MMP assays of the clausenidin-treated HepG2 and HT-29 ce lls were also performed to determine the mode of cell death. In addition, apoptosis-re lated genes and proteins were also analyzed using qPCR and Western blot respectively to further verify the effects of clausenidin on HepG2 and HT-29 cells. The IC50 of clausenidin in HepG2 and HT-29 cells was 7.7 and 13.8 μg/mL at 72 hours of treatment, respectively. The results reveal that clausenidin induced G0/G1 and G2/M cell cycle arrest of HepG2 cells in a dose- and time-dependent manner. Clausenidin also caused depolarization of the mitochondrial membrane that resulted in the release of cytochrome C and significant (p<0.05) upregulation of Bax, Apaf-1, Smac, Caspase-3 and -9 proteins, suggesting involvement of the mitochondria pathway of apoptosis. It was also observed that the caspase-8, TNFR1, TRAIL, FADD and Fas proteins, which are key regulators of the extrinsic pathway of apoptosis were upregulated. Gene studies showed significant (p<0.05) increases in caspase-8 and -9 ex pression that further corroborates the involvement of the extrinsic and intrinsic pathways in the apoptosis of clausenidin-treated HepG2 cells. The JNK, Bax, Apaf 1, cytochrome C, p53 and p21 genes were also found to be significantly (p<0.05) upregulated while Bcl-2, Bcl-x and HSP70 were downregulated. The findings suggest that clausenidin also suppressed the inducers of angiogenesis in HepG2 cells. Clausenidin-mediated apoptosis was evident by the increase in DNA fragmentation, typical microscopic and ultrastructural features of apoptosis. Clausenidin induced responses in the HT-29 cells like that of the HepG2 cells, except that it did not cause significant (p>0.05) change in caspase-8, JNK and VEGF protein expressions. The HT-29 cells treated with clausenidin entered a G0/G1 cell cycle arrest. These cells also underwent depolarization of mitochondrial membrane resulting in cytochrome C release and subsequent increase in caspase-9 and Bax protein expressions that resulted in the activation of the intrinsic pathway of apoptosis. Clausenidin induced activation of caspase-3 that caused fragmentation of DNA and nuclei of the HT-29 cells, which are hallmarks of apoptosis. Upon treatment with clausenidin, HT-29 cells also showed increased production of ROS that is postulated to contribute to their death. The clausenidin-treated HT-29 cells like the HepG2 cells showed typical features of apoptosis although some cells underwent necrosis. In conclusion, the study showed clausenidin isolated from C. excavata induced death of the HepG2 and HT-29 cells especially via apoptosis. Thus, clausenidin has the potential to be developed as a therapeutic compound for the treatment of liver and colon cancers.